Food Protein-Induced Allergic Proctocolitis: The Effect of Maternal Diet During Pregnancy and Breastfeeding in a Mediterranean Population - Vassilopoulou, Emilia; Feketea, Gavriela; Konstantinou, George N.; Zekakos Xypolias, Dimitris; Valianatou, Mina; Petrodimopoulou, Maria; Vourga, Vasiliki; Tasios, Ioannis; Papadopoulos, Nikolaos G. (Frontiers in Nutrition, 2022)
Background The aim of the current investigation was to explore the association of food protein-induced allergic proctocolitis (FPIAP) with the maternal diet during pregnancy and breastfeeding in Greek infants. Methods A multicenter retrospective case-control study was conducted in 6 regions in Greece, with 96 mothers of infants with and 141 mothers of infants without a history of FPIAP. Maternal dietary habits during pregnancy and breastfeeding were evaluated with the following validated questionnaires: (a) The Mediterranean Diet Score and (b) The Mediterranean Oriented Culture-Specific Semi-Quantitative Food Frequency Questionnaire. Results FPIAP was associated with cow's milk (83.6%), egg (7.3%), wheat (6.4%), and beef (6.4%) in the maternal diet. Adherence to Mediterranean Diet was similar among the mothers. Mothers of FPIAP infants consumed more vegetables. Elastic net prediction models showed that, in this Mediterranean population, increased consumption during pregnancy and lactation of common allergens, whole grain products, homemade food, fish and shellfish, and fruits was associated with a decreased risk of FPIAP. Conversely, a high intake of vegetables, sugar and total fat, and non-stick/grilled cooking, were associated with increased risk of FPIAP, as was a high intake of salt and white flour during lactation only. Conclusions Components of a maternal Mediterranean Diet may protect against FPIAP when traditional cooking methods are adopted and fish, fruit, and whole wheat products are consumed frequently during pregnancy and breastfeeding.